INTRANET NETWORK BUILDING IN MENDALA USING WINDOWS 2000 SERVER TRAVEL - Rico Suherman; Fitri Sjafrina, Skom, MM Fitri Sjafrina, Skom, MM (Jurnal Sistem Informasi, 2008)
In the current era of reform, the need for information is very important, especially inthe business world. Therefore, the application of intranet technology is one of theappropriate solution for the exchange of information, both internal and externalenvironments of an organization. With these scientific writing, may be able to helpofficers in serving the reservations and purchase tickets by prospective passengers.The author helped develop the Mandala Travel intranet using windows 2000 serverand Apache web server.At this time in performing services Travel Mandala airline ticket sales are still usingconventional means, such as by telephone. So the sales report was submitted by eachofficer.In completing this writing, the author helps build a network of LAN and intranetnetworks realize Travel on Mandala, to assist officers in serving the sale of airlinetickets. In this study, the authors connect with the local IP public IP 118.137.53.79obtained after registering and subscribing to an Internet Service Provider (ISP) Fasnetusing the Windows 2000 Server.The need for information is very important, especially in the business world such asairline ticket sales agent. The author hopes to build an intranet network on TravelMandala scope of work, then the ticket sales information can be conveyed to therelevant parts to the leadership.